Lateral Load-Resisting System Using Mass Timber Panel for High-Rise Buildings - Chen, Zhiyong; Chui, Ying-Hei (Frontiers in Built Environment, 2017)
As global interest in using engineered wood products in tall buildings intensifies due to the ‘green’ credential of wood, it is expected that more tall wood buildings will be designed and constructed in the coming years. This, however, brings new challenges to the designers. One of the major challenges is how to design lateral load resisting systems with sufficient stiffness, strength and ductility to resist strong wind and earthquakes. In this study, a hybrid lateral load resisting system (LLRS) using mass timber on stiff podium was developed for high-rise buildings in accordance with capacity-based design principle. The LLRS consisted of shear walls and a shear core, both made of structural composite lumber, connected with dowel-type connections and heavy-duty HSK (wood-steel-composite) system. The wood-based panel-to-panel interface was designed to be the main energy dissipating mechanism of the system. This proposed system was implemented in the design of a hypothetical 20-storey building. A refined finite element model of the building was developed using general-purpose finite element software, ABAQUS. The wind-induced and seismic response of the building model was investigated by performing linear static and nonlinear dynamic analyses. The analysis results proved that the proposed LLRS using mass timber was suitable for high-rise buildings. This study provides a valuable insight into the structural performance of lateral load resisting system constructed with mass timber panels as a viable option to steel and concrete for high-rise buildings.